Emerging Adults with Chronic Illness Pursuing and Enhancing Leisure. (1st January 2016) - Snelgrove, Ryan; Wood, Laura; Carr, Kelly
Abstract : The purpose of this study is to develop an understanding of the adjustment process undertaken by emerging adults living with a chronic illness in their pursuit and enjoyment of leisure. A theoretical focus is placed on the processes of selection, optimization, and compensation. Semi-structured interviews were conducted with 27 participants who have a chronic illness. Participants' experiences were rooted much more in triumph rather than loss. Selection was influenced by a consideration of uncertainty, a desire to avoid potential embarrassment, and an acceptance or rejection of constraints. Three types of approaches that helped them optimize their leisure experience involved participants shaping their perspectives about leisure and life, enhancing resources to make leisure possible, and by living through pain and discomfort. Responding to challenges that might otherwise limit their participation or enjoyment in leisure, participants prepared for possible incidents, received support from others, and confronted negative situations.